An assessment of foreign direct investment to transition economies in the context of contemporary theories - Aliyev, Mehdi (My University, 2011)
Yirmi yıl önce Sovyetler Birliği’nin çöküşünden sonra, eski Sovyetler mekanındaki ülkeler ile Merkezi ve Doğu Avrupa ülkeleri planlı ekonomiden piyasa ekonomik sistemine geçişlerini ilan ettiler. Geçiş ekonomilerine Doğrudan Yabancı Yatırım (DYY) akışı bu ülkelerin ekonomik dönüşümü ve dünya ekonomisine entegrasyonu açısından önemli bir katkı olarak görülmektedir. Geleneksel olumlu etkilerinin yanı sıra, piyasa ekonomik sistemini geçiş ekonomilerine tanıtması anlamında DYY’lar bu ülkeler için özellikle önem arzetmektedir. Bu çalışmada Merkezi ve Doğu Avrupa ve Bağımsız Devletler Topluluğu’nda olan geçiş ekonomilerine DYY akışı, üretimin uluslararasılaşması teorileri kapsamında değerlendirilmektedir. Bu değerlendirmenin amacı hangi DYY teorisinin söz konusu ülkelere gelen DYY’ları daha kapsamlı bir şekilde açıkladıgını ortaya çıkarmak ve bu teori bazında politik çıkarımları belirlemektir.

After the dissolution of the Soviet Union two decades ago, countries that emerged in Soviet orbit and countries of Central and Eastern Europe declared their transition from planned to a market economic system. Foreign Direct Investment (FDI) flows into the transition economies are viewed as a significant contribution to the economic transformation of these economies and to their integration to the world economy. For the transition economies, FDI is particularly important in a sense that along with the traditional positive impacts, this type of investment introduces market economic system to these economies. This study assesses FDI flows into the transition economies of the Central and Eastern Europe and Commonwealth of Independent States in the context of theories of internationalization of production in order to find out which theory provides relatively comprehensive explanation to the inward FDI of these countries and determine the policy implications on the basis of that theory.
Keywords: Ekonomi; Yabancı Yatırımlar